Lasciare il bambino in macchina. Amnesia comune o malattia? - Riggio, Martino (Il sogno della farfalla, 2019)
In this article the author discusses how, according to the psychiatric scientific literature, the tragic events of children abandoned in the car by their parents should be attributed to psychogenic or dissociative amnesia. These kinds of episodes would not be manifestation of a severe mental illness, and, as a consequence, it is also stated that they could occur to any common person. After refusing these propositions, the author highlights the existence of a form of memory unknown to the subject, as for instance the one appearing in dreams. The Human Birth Theory formulated by Massimo Fagioli, identifies the origin of this memory at birth, when the emergence of an internal image realizes the first “knowledge” of an individual. Therefore this represents the first unconscious memory. The loss of this latter it is not an accidental fact which could occur to anybody but rather a serious event leading to a lack of affection and stolidity.